(untitled) (Agricultural Engineering, 2017)
The paper presents main provisions of methodology of manure utilization systems evaluation. All costs, starting with the costs related to manure cleaning in premises to the costs of increasing the biological yield obtained from its use, including the soil fertility value changes, were considered. The target function is offered a minimum of complex costs of entering the required amount of nutrients and organic matter per unit area for the planned yield. The effective technical solutions of calculations based on the proposed method include: construction of a boom conveyor with a hydraulic drive and described performance, scraper and screw types of conveyors, automatic scraper loading installation of manure from livestock buildings. The proposed solutions will reduce losses of nutrients by 50-70%, and will allow production of 20 million tons of grain annually.